KONTRIBUSI AJARAN AGAMA DALAM MELESTARIKAN INTERAKSI SOSIAL - Kamaluddin Kamaluddin (Studia Sosia Religia, 2022)
For survival, values or norms (regulations) are needed, which function to encourage individuals to fulfill the obligations stipulated in society. the command to carry out these obligations is sourced from religious teachings. Religious teachings have a contribution and coercive power because religious teachings are seen as something sacred, which if ignored, a person will get a frightening reward (sin).